Advanced and smart nanocarriers for pharmaceutical applications - Mazzotta, Elisabetta; Andò, Sebastiano; Muzzalupo, Rita (Università della Calabria, 2020)
The application of nanotechnology in drug formulation has made significant headway over the last decade. Nanoscale controlled release systems allow to revalue and reformulate old drugs through targeted delivery to the desired pathological site, improving therapeutic efficiency and reducing side effects. This innovative modality of drug delivery aims to create personalized, safer and effective treatments. A great interest of the academic and industrial research is focused on the design and development of advanced nanocarriers since is a profitable way in terms of costs, times and risks than the discovery of new drugs. Herein, an extensive variety of nanocarriers systems composed of different materials including lipids, polymers and non-ionic surfactants have been proposed for different pharmaceutical applications. Specifically, the carriers have been tailor-made designed to improve drug photostability, enhance skin permeation and realize smart tools for tumor target therapy.
UNIVERSITY OF CALABRIA Department of Pharmacy and Health and Nutritional Sciences PHD IN TRANSLATIONAL MEDICINE Ciclo XXXII
Keywords: Nanotechnology; Target delivery; Topical Therapy; Cancer therapy; Drug Photoprotection